The impact of the Covid-19 pandemic on the life of Italian mobile peoples - Pontrandolfo, Stefania; Solimene, Marco; Secchi, Laura (Antropologia Pubblica, 2024)
This report provides an account of the research conducted in Italy and relates to the most relevant and evident effects of the pandemic on the lives of some families of nomadic service providers (mainly Sinti fairground workers and Roma scrap metal collectors from Emilia Romagna). This was part of a wider research conducted within the framework of the “Re-imagining Development for Mobile and Marginalised Peoples” (ReDeMP) project (financed by the John Fell Fund at Oxford University in 2021) on the sedentist bias in development policies towards mobile peoples. What emerged from research was an explicit sedentist bias pervading housing policies toward Roma and Sinti in Italy, in the guise of the restricted access to social services as a result of the bureaucratic trap of registered residence; a more implicit sedentist bias in Italian work regulations, which hamper the itinerant activities of fairground workers and scrap metal collectors.